2014
DOI: 10.5194/bg-11-3757-2014
|View full text |Cite
|
Sign up to set email alerts
|

On the effects of circulation, sediment resuspension and biological incorporation by diatoms in an ocean model of aluminium*

Abstract: The distribution of dissolved aluminium in the West Atlantic Ocean shows a mirror image with that of dissolved silicic acid, hinting at intricate interactions between the ocean cycling of Al and Si. The marine biogeochemistry of Al is of interest because of its potential impact on diatom opal remineralisation, hence Si availability. Furthermore, the dissolved Al concentration at the surface ocean has been used as a tracer for dust input, dust being the most important source of the bio-essential trace element i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 78 publications
3
35
0
Order By: Relevance
“…Thus it is now shown that the energetic bottom flow of the DSOW in the West Atlantic leads to elevated [Al], whereas the relatively stagnant bottom waters in the northeast basin have lower concentrations (Hall and Measures, 1998). The sediment resuspension source for Al is also confirmed in an ocean general circulation model that includes biogeochemistry and Al cycling (Van Hulten et al, 2014) and now also confirmed for the northwestern Atlantic basin by Measures et al (in press). …”
Section: North Atlantic Deep Watersupporting
confidence: 73%
See 1 more Smart Citation
“…Thus it is now shown that the energetic bottom flow of the DSOW in the West Atlantic leads to elevated [Al], whereas the relatively stagnant bottom waters in the northeast basin have lower concentrations (Hall and Measures, 1998). The sediment resuspension source for Al is also confirmed in an ocean general circulation model that includes biogeochemistry and Al cycling (Van Hulten et al, 2014) and now also confirmed for the northwestern Atlantic basin by Measures et al (in press). …”
Section: North Atlantic Deep Watersupporting
confidence: 73%
“…3a and b). Elevated [Si] in bottom waters has been postulated to prevent release of Al from aluminosilicates in sediments (Mackin and Aller, 1986 (their equation (3) and related text); Van Hulten et al, 2014). Conversely, the low [Si] in the DSOW favours release and accumulation of [Al] in bottom water DSOW.…”
Section: North Atlantic Deep Watermentioning
confidence: 99%
“…1, has been employed for many other studies concerning trace metals, as well as large-scale ocean biogeochemistry (e.g. Gehlen et al, 2007;Arsouze et al, 2009;Dutay et al, 2009;Tagliabue et al, 2010;Van Hulten et al, 2014). The model simulates the biogeochemical sources and sinks of 24 prognostic tracers, including five limiting nutrients (Fe, PO 4 , Si(OH) 4 , NO 3 , and NH 4 ) Two phytoplankton groups (nanophytoplankton and diatoms) and two zooplankton size classes (microzooplankton and mesozooplankton) are represented in PISCES.…”
Section: The Biogeochemical Global Ocean Modelmentioning
confidence: 99%
“…However, a recent comparison of thirteen Fe-incorporating GBMs found that 'all models struggle to reproduce many aspects of the observed spatial patterns' (Tagliabue et al, 2016). For other metals, such as Mn and Al, good agreement between observed and modeled values have been achieved in select parts of the global ocean (van Hulten et al, 2017(van Hulten et al, , 2014(van Hulten et al, , 2013. However, each GBM still struggles to replicate certain processes (e.g.…”
Section: Constraining the Particulate Export Of Trace Metalsmentioning
confidence: 99%